2019
DOI: 10.3390/en12203987
|View full text |Cite
|
Sign up to set email alerts
|

Energy Scheduling Using Decision Trees and Emulation: Agriculture Irrigation with Run-of-the-River Hydroelectricity and a PV Case Study

Abstract: Agriculture is the very backbone of every country. Unfortunately, agricultural sustainability is threatened by the lack of energy-efficient solutions. The threat becomes more evident with the constantly growing world population. The research community must, therefore, focus on resolving the problem of high energy consumption. This paper proposes a model of energy scheduling in agricultural contexts. Greater energy efficiency is achieved by means of PV (photovoltaics) and hydropower, as demonstrated in the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
0
8
0
1
Order By: Relevance
“…The method used for energy efficiency analysis [18,19,31,32] is based on the definition of direct and indirect energy inputs, calculation of the energy output for given plant production. Based on these data in wheat and sugar beet production specific energy input, energy output-input ratio, energy productivity and net energy gain were estimated as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used for energy efficiency analysis [18,19,31,32] is based on the definition of direct and indirect energy inputs, calculation of the energy output for given plant production. Based on these data in wheat and sugar beet production specific energy input, energy output-input ratio, energy productivity and net energy gain were estimated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Today's agricultural practices still lack energy optimization measures, leading to high energy consumption [18]. One way to optimize energy consumption is to determine the efficiency of methods and techniques used [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a research study proposed an energy management model in farms to facilitate the use of solar systems and hydropower. 22 The study simulated a farm near a river to use the run-of-the-river hydroelectricity in the irrigation systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study evaluated the energy consumption of the irrigation systems to justify the cost‐effective usage of the suggested solar‐powered irrigation systems. Moreover, a research study proposed an energy management model in farms to facilitate the use of solar systems and hydropower 22 . The study simulated a farm near a river to use the run‐of‐the‐river hydroelectricity in the irrigation systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the same statement, it is shown that between 14% to 30% of these GHG emissions are related to the fossil fuels that have been used in this sector for the pump water and irrigation purposes. This shows the need for exchanging fossil fuels to Renewable Energy Resources (RERs) in the agriculture sector [8].…”
Section: Introductionmentioning
confidence: 99%